2016
DOI: 10.1111/papq.12157
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic and non‐Epistemic Theories of Remembering

Abstract: Contemporary memory sciences describe processes that are dynamic and constructive. This has led some philosophers to weaken the relationship between memory and epistemology; though remembering can give rise to epistemic success, it is not itself an epistemic success state. I argue that non-epistemic (causal) theories will not do; they provide neither necessary nor sufficient conditions for remembering that p. I also argue that the shortcomings of the causal theory are epistemic in nature. Consequently, a theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…There are a few contemporary defenders of epistemic (James, 2017) and even empiricist (Byrne, 2010) theories of memory, but the overwhelming majority of philosophers of memory today endorse theories that recognizably descend from the causal theory of memory as formulated by Martin and Deutscher (Debus, 2017). It is on a subset of these that we focus here.…”
Section: Contentless Memory Traces and (Post)causal Theories Of Memorymentioning
confidence: 99%
“…There are a few contemporary defenders of epistemic (James, 2017) and even empiricist (Byrne, 2010) theories of memory, but the overwhelming majority of philosophers of memory today endorse theories that recognizably descend from the causal theory of memory as formulated by Martin and Deutscher (Debus, 2017). It is on a subset of these that we focus here.…”
Section: Contentless Memory Traces and (Post)causal Theories Of Memorymentioning
confidence: 99%
“…Hence, if you can be recognised as remembering that p, then you are epistemically permissible to believe that p. Premise 2 is a variant of mEE‐K, according to which if you epistemically permissibly believe that p, then you can be recognised as knowing that p, provided that the norm of belief is knowledge. Putting premises 1 and 2 together, it can be concluded that whenever one can be recognised as remembering that p, one can also be recognised as knowing that p. In brief, remembering entails knowing, which is the central claim of the epistemic theory of knowledge (see James, 2017, p. 122 for a long list of proponents; see also Moon, 2013 and Craver, 2020 for relevant discussions). Therefore, if premise 1 is true, then mEE‐K implies ETM.…”
Section: Memory Belief and Knowledgementioning
confidence: 99%
“…As far as what is variously described as propositional, semantic or factual memory is concerned, the idea that memory should be defined as the retention of knowledge in fact has a long history (see, e.g., Annis 1980;Ayer, 1956;Malcolm, 1963;Naylor, 1971;Zemach, 1968). For discussions of 'epistemic theories of memory' in this sense, see, e.g., James (2017) and Adams (2011).…”
Section: The Target Explanandummentioning
confidence: 99%
“…to that question, the question itself needs to be distinguished from questions about the neural underpinnings of episodic memory (see also James 2017).…”
mentioning
confidence: 99%